VAGINOPLASTY WITH BILATERAL ISLANDED PUDENDAL THIGH FLAPS - Ajmal, Samira; Yusuf, Kanwal (Journal of Ayub Medical College Abbottabad, 2010)
Background: Vaginal agenesis is the most common congenital deformity of female pelvis and vaginal reconstruction remains a surgical challenge. There are various surgical and non-surgical techniques described for the reconstruction of neovagina. We have used pudendal thigh flaps raised on either side of the labia to reconstruct the vagina in 19 patients. This study is carried out in the Department of plastic and reconstructive surgery, Hayatabad medical complex Peshawar to evaluate the functional and aesthetic outcome of vaginoplasty with bilateral pudendal thigh flaps. Methods: Vaginal reconstruction was done with bilateral islanded pudendal thigh flaps, in 19 consecutive patients with vaginal atresia, during 5 years, from Aug 2004 to Aug 2009. The flaps were raised on either side of labia and sutured to each other in midline to form a vaginal tube. This neo-vagina was inserted into the space between the rectum and bladder and anchored to the deep pelvic tissues. Results: Out of 19, eleven patients (58%) were diagnosed with Mayer Rokitansky Kauser Hauser Syndrome and 8 (42%) with isolated vaginal atresia. The mean vaginal length and width was 9.2 and 4.3 cm respectively one year post operatively. Conclusion: This method of vaginoplasty is simple, safe, and reliable and has shown satisfactory functional and cosmetic results. The reconstructed vagina has a natural angle and is sensate in its lower part. No postoperative stenting or dilatation is required. The donor site in the groin can be closed primarily and the scar is well hidden in the groin crease. Keywords: Vaginoplasty, vaginal reconstruction, vaginal atresia, pudendal thigh flaps